Approximation modeling framework for elastic-plastic stress-strain fields near cracks with a small finite crack tip radius. (October 2022) - Ince, A.; Glinka, G.
Highlights: A new modeling framework is developed to compute elastic–plastic stresses and strains ahead of a crack tip. Non-linear finite element analysis data of a SAE 1070 steel plate is used for the model verification. The proposed modeling approach provides efficient and accurate predictions. The proposed approach can be used for fatigue crack growth analysis by accounting for elastic–plastic stresses and strains around the crack tip. Abstract: A number of studies have shown that fatigue crack growth behavior is controlled by elastic–plastic strains and stresses localized in the vicinity of a propagating crack tip. Stress and strain distributions ahead of the crack tip are critical to crack growth analysis of structural components. Such analyses are very important in the case of engineering applications involving safe and cost-effective designs and the aspects of damage tolerance. Although Finite Element (FE) analysis using commercial software packages can be employed to compute local stresses and strains around the crack tip, such numerical analysis methods are expensive in engineering applications in terms of computational efficiency, labor intensity and data storage purposes. Therefore, a new approximation-based modeling framework has been developed to compute elastic–plastic stresses and strains distributions ahead of a stationary crack tip in plane stress conditions. The proposed modeling approach has been verified based on numerical non-linear finite element (FE) analysis data involving a SAE 1070 steel plate with two different edge crack lengths. The predicted results show that the proposed model enables efficient and accurate predictions of elastic–plastic stresses and strains around the crack tip induced by cyclic axial loading.